2019
DOI: 10.1016/j.ijrobp.2019.06.1789
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Features from PSMA PET for Intraprostatic Tumor Discrimination and Characterization in Patients with Prostate Cancer. a Comparison Study with Histology Reference

Abstract: therapy to the prostate compared to 5.6 years for patients who did receive radiation therapy to the prostate. Conclusion: Similar to newly diagnosed metastatic prostate cancer with a low metastatic burden limited to the bone, M1a prostate cancer may also derive a significant overall survival benefit from receiving radiation therapy to the primary prostate tumor. The use of prostate-directed radiation therapy for M1a patients should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prostate-specific membrane antigen positron emission tomography (PSMA-PET) has recently been established for initial staging in primary PCa patients (3). It is also increasingly used in order to improve intraprostatic lesion detection (4)(5)(6), focal therapy guidance (7) and noninvasive PCa characterization (8). Most of the studies evaluated 68Ga-PSMA-11 as radiopharmaceutical.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate-specific membrane antigen positron emission tomography (PSMA-PET) has recently been established for initial staging in primary PCa patients (3). It is also increasingly used in order to improve intraprostatic lesion detection (4)(5)(6), focal therapy guidance (7) and noninvasive PCa characterization (8). Most of the studies evaluated 68Ga-PSMA-11 as radiopharmaceutical.…”
Section: Introductionmentioning
confidence: 99%
“…PSMA PET-CT is gaining increasing importance for initial prostate cancer staging and has also been employed in radiomics analyses. For example, it was shown that PSMA PET-CT radiomics can distinguish between intermediate and high-risk prostate cancer [174]. Although this may have the potential to better select patients for tumor biopsies and treatment approach, such a methodology is not yet used in routine clinical practice for patient management.…”
Section: Clinical Relevance: Impact On Patients Managementmentioning
confidence: 99%